Neurobehavioral Analysis of Ethanolic Extract of Roots and Rhizomes of Acorus calamus in 6-hydroxydopamine Hydrobromide-induced ADHD Neonatal Rat Model – An Observational Study - Mariyappan Kousalya; Palayyan Muralidharan; Hanish Singh Jayasingh Chellammal (World Journal of Traditional Chinese Medicine, 2024)
Background: An imbalance in Nor-adrenaline and Dopamine neurotransmitter levels in the brain is the reason for the development of Attention Deficit Hyperactivity Disorder (ADHD) which is a neurodevelopmental disorder. 6-Hydroxy Dopamine hydrobromide injection in the brain destroys catecholamine receptors thereby inducing, ADHD and expressing ADHD symptoms such as hyperactivity, inattention, anxiety, and impaired cognitive function. Aims and Objectives: Our aim is to analyze the antagonistic effect of 6-Hydroxy Dopamine by the ethanolic extract of the Acorus calamus in Neonatal rats. Settings and Design: The study was conducted in neonatal rats and analyzed the three main signs of ADHD-like behaviour in 6-OHDAHBr rats on attention, and impairment. The model identified distinct co-occurring symptoms, marble burying behaviour. The animals were sacrificed and histopathological analysis was performed. Materials and Methods: Rats were divided into 5 groups. Control, Induced control, Standard, test drug of low and high dose. The behavioural analysis was studied on days 7, 14, and 21 using pole climbing, water maze, marble burying. Statistical Analysis Used: One-way ANOVA with multiple Graphpad prism version 9.0. Results: The extract shows significant improvement in reducing ADHD symptoms in dose-dependent manner. The model's validity is further supported by a histological investigation that reveals dopamine depletion, changes in cortical thickness, and anomalies in the neurons of the anterior cingulate cortex. Conclusions: The study concludes that neonatal dopamine deprivation causes behavioural abnormalities that are comparable to those seen in patients, making it a useful model for researching the pathophysiological mechanisms underlying ADHD and discovering potential treatment targets.